Intensive Interval Training on Sprint Running Speed in Junior High School Extracurricular Activities - Taufik Rahman; Syamsuramel Syamsuramel; Herri Yusfi; Destriani Destriani (Universitas Sriwijaya, 2023)
This study aims to determine the effect of the intensive interval training method on sprint speed in the extracurricular activities of Atap Indralaya 4 Public Junior High School. This research is a type of quasi-experimental research using a design in the form of a pretest posttest one group design. With the independent variable in the form of intensive interval training and the dependent variable is the result of sprint running speed. The population used in this study amounted to 67 people and the research sample was 30 students using random sampling. The instrument used is a 60 meter sprint test. The treatment given to students is intensive interval training, the frequency is carried out 3 times a week and it is carried out for 6 consecutive weeks. In the data analysis and research results using the t-test statistic, a significant level ? = 0.05 obtained tcount (26.88) while ttable (1.701) then tcount > ttable so that the hypothesis can be accepted, that using the intensive interval training method can increase the results of running speed student sprints in extracurricular activities at Atap Indralaya Middle School 4.